2022
DOI: 10.3390/ijerph19159692
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Stress Coping Styles and Hope for Success among Graduate Students and High School Graduates during the COVID-19 Pandemic: The Moderating Role of Remote Learning

Abstract: The COVID-19 pandemic has significantly influenced the area of education, in terms of both teaching and learning effectiveness. The aim of the study was to compare groups of high school graduates and graduate students. The Coping Inventory in Stressful Situations (CISS), State and Trait Anxiety Inventory (STAI), Hope for Success Questionnaire (KNS), and our own questionnaire were used in the study. The results of the research show that the group of high school graduates, compared to the graduate students, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…When military personnel consider their future paths after discharge, it may be inferred that groups with lower educational attainment may experience higher stress levels. In contrast to previous study, 37 which showed higher levels of anxiety and stress in high school graduates compared to graduate students, our study found a higher prevalence of high‐risk stress in individuals with education levels beyond undergraduate studies. Further research is necessary to confirm this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…When military personnel consider their future paths after discharge, it may be inferred that groups with lower educational attainment may experience higher stress levels. In contrast to previous study, 37 which showed higher levels of anxiety and stress in high school graduates compared to graduate students, our study found a higher prevalence of high‐risk stress in individuals with education levels beyond undergraduate studies. Further research is necessary to confirm this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study showed that undergraduate nursing students with higher personal resilience (positive coping style) had a lower stress during COVID-19 pandemic in India 53 . Similarly, students who had an emotion-focused coping style had a higher level of anxiety during the COVID-19 pandemic in Poland 54 . A two-phase longitudinal study showed that during the COVID-19 pandemic, Chinese children with activeavoidance coping style had a low level of anxiety and depression 55 .…”
Section: Discussionmentioning
confidence: 94%
“… 53 Similarly, students who had an emotion-focused coping style had a higher level of anxiety during the COVID-19 pandemic in Poland. 54 A two-phase longitudinal study showed that during the COVID-19 pandemic, Chinese children with active-avoidance coping style had a low level of anxiety and depression. 55 Negative coping style associated with psychological distress in Chinese college students.…”
Section: Discussionmentioning
confidence: 99%